Tryal (Schooner) logbook - Tryal (Schooner)
Logbook (39 pages; 1832 March 11-1833 January 20) of a schooner sailing in the West Indies under Jesse Mallett, master.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Mallett, Jesse; Logbooks -- United States -- 19th century; Ship's papers -- 19th century; West Indies -- Description and travel